Relevansi Kompetensi Guru Berdasarkan UU No 14 Tahun 2005 di Era Society 5.0 - Ahmad Rafiky; Fuji Rahmadiah; Husni Zakiyah; Rully Hidayatullah; Hadeli (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
To complete their duties, a teacher must possess competence. Teachers must understand various approaches, strategies, methods, and digital media related to learning in today's technological era. If teachers cannot keep up with the use of technology in education in the digital age, students who are active and quick to adapt to technology will become a significant challenge. Therefore, to achieve effective and efficient learning outcomes in this technological era, teachers must possess digital skills.  In this article, a descriptive qualitative research method is used by collecting various literature sources. According to Law No. 14 of 2005 concerning Teachers and Lecturers, Article 8 states that every teacher must possess teaching competence. Competence refers to a set of knowledge, skills, and behaviors that teachers must have, internalize, and master in carrying out their professional duties.  Various studies have proven the importance of teacher competence in the educational and learning process. Among them is research conducted by Kay in 1980, as cited by Rohmat Mulyana (2003:1), which concluded that a teacher's teaching ability is one of the variables that significantly influences students' academic competence.  The Republic of Indonesia Law No. 14 of 2005 on Teachers and Lecturers stipulates four basic competencies that teachers must possess: pedagogical, personal, professional, and social competencies.  The purpose of this study is to explain the digital competencies that teachers must have to ensure successful learning activities in the digital era. In conclusion, teachers must possess digital skills to face the challenges of teaching in the digital age.